Executive summary of the 14th HHT international scientific conference: executive summary - Ola, Roxana; Hessels, Josefien; Hammill, Adrienne; Friday, Cassi; Clancy, Marianne; Al-Samkari, Hanny; Meadows, Stryder; Iyer, Vivek; Akhurst, Rosemary (Angiogenesis, 2023)
Hereditary Hemorrhagic Telangiectasia (HHT) is an autosomal dominant vascular disorder characterized by small, dilated clustered vessels (telangiectasias) and by larger visceral arteriovenous malformations (AVMs), which directly connect the feeding arteries with the draining veins. These lesions are fragile, prone to rupture, and lead to recurrent epistaxis and/or internal hemorrhage among other complications. Germline heterozygous loss-of-function (LOF) mutations in Bone Morphogenic Protein 9 (BMP9) and BMP10 signaling pathway genes (endoglin-ENG, activin like kinase 1 ACVRL1 aka ALK1, and SMAD4) cause different subtypes of HHT (HHT1, HHT2 and HHT-juvenile polyposis (JP)) and have a worldwide combined incidence of about 1:5000. Expert clinicians and international scientists gathered in Cascais, Portugal from September 29th to October 2nd, 2022 to present the latest scientific research in the HHT field and novel treatment strategies for people living with HHT. During the largest HHT scientific conference yet, participants included 293 in person and 46 virtually. An impressive 209 abstracts were accepted to the meeting and 59 were selected for oral presentations. The remaining 150 abstracts were presented during judged poster sessions. This review article summarizes the basic and clinical abstracts selected as oral presentations with their new observations and discoveries as well as surrounding discussion and debate. Two discussion-based workshops were also held during the conference, each focusing on mechanisms and clinical perspectives in either AVM formation and progression or current and future therapies for HHT. Our hope is that this paper will represent the current progress and the remaining unanswered questions surrounding HHT, in order to serve as an update for those within the field and an invitation to those scientists and clinicians as yet outside of the field of HHT.
Gesehen am 08.10.2024